The Effectiveness of Communicative Language Teaching in Developing Oral Proficiency among EFL Students The Case Study of 3rd year EFL students at Mouhamed Cherif Mesaadia University , Souk Ahras - Lamisse REMIKI (My University, 2025)
Abstract Fluency and effectiveness in a language are essential indicators of communicative skill, particularly in the context of foreign language acquisition. In English as a Foreign Language (EFL) classroom, speaking is often regarded as the most challenging skill to master, even though it remains the most sought-after for practical communication. While students often receive substantial training in grammar and vocabulary, they frequently lack opportunities to engage with authentic English materials, resulting in difficulties in participating in real conversations. This disconnect between academic knowledge and real-world application typically leads to low confidence, hesitation, and poor performance in oral communication. This study aims to demonstrate the effectiveness of the Communicative Language Teaching (CLT) approach in enhancing oral proficiency among EFL students. To test the primary hypothesis that implementing the CLT approach improves students' speaking skills, a mixed –method approach involving both quantitative and qualitative research methods was employed. Classroom observations and questionnaires were administered to a sample of 40 third-year EFL students out of a total population of 93 students and 6 teachers at Souk-Ahras University. The observations focused on how CLT is applied in EFL classrooms and its efficacy in enhancing students' speaking abilities. Simultaneously, the questionnaire was developed to collect students' attitudes and needs concerning the teaching-learning process, as well as to assess teachers' perspectives on the CLT approach in EFL classes. The study results indicate that the CLT approach is effective in positively impacting learners' speaking skills, providing them with a comfortable and supportive environment for developing oral proficiency. -------------- الملخص تُعد الطلاقة والفعالية في اللغة من المؤشرات الأساسية على الكفاءة التواصلية، لاسيما في سياق تعلم اللغات الأجنبية. ويُعتبر التحدث في فصول اللغة الإنجليزية كلغة أجنبية من أكثر المهارات تحدياً لإتقانها، رغم كونه المهارة الأكثر طلبًا لأغراض التواصل العملي. وعلى الرغم من حصول الطلاب في كثير من الأحيان على تدريب مكثف في قواعد اللغة والمفردات، إلا أنهم غالباً ما يفتقرون إلى الفرص الكافية للتفاعل مع مواد أصلية باللغة الإنجليزية، مما يؤدي إلى صعوبات في خوض محادثات حقيقة. ويؤدي هذا الانفصال بين المعرفة الأكاديمية والتطبيق الواقعي إلى ضعف الثقة بالنفس، والتردد، والأداء المتدني في التواصل الشفهي. تهدف هذه الدراسة إلى إبراز فعالية منهج التدريس التواصلي في تعزيز الكفاءة الشفوية لدى طلبة اللغة الإنجليزية كلغة أجنبية. ولاختبار الفرضية الأساسية المتمثلة في أن تطبيق هذا المدخل يساهم في تطوير مهارات التحدث لدى الطلاب، تم اعتماد منهجية بحثية تجمع بين الأسلوبين الكمي والنوعي. شملت الدراسة ملاحظات صفية واستبيانات تم توزيعها على عينة مكونة من 40 طالبًا من السنة الثالثة من أصل 93 طالبًا، بالإضافة إلى 6 أساتذة بجامعة سوق أهراس. ركزت الملاحظات الصفية على كيفية تطبيق المدخل التواصلي في أقسام اللغة الإنجليزية ومدى فعاليته في تحسين القدرات الشفوية للمتعلمين. في الوقت ذاته، صُممت الاستبيانات لجمع آراء الطلاب حول عملية التعليم والتعلم، وتقييم وجهات نظر الأساتذة تجاه هذا المدخل في فصول اللغة الإنجليزية. تشير نتائج الدراسة إلى أن منهج التدريس التواصلي يحقق تأثيرًا إيجابيًا في تطوير مهارات التحدث لدى الطلاب، من خلال توفير بيئة تعليمية داعمة ومريحة تعزز من كفاءتهم الشفوية. --------------- Résumé La fluidité et l'efficacité dans l’usage d'une langue constituent des indicateurs fondamentaux de la compétence communicative, en particulier dans le cadre de l'apprentissage des langues étrangères. En classe d'anglais langue étrangère (EFL), l'expression orale est souvent perçue comme la compétence la plus difficile à maîtriser, Malgré une formation approfondie en grammaire et en vocabulaire, les étudiants manquent fréquemment d'exposition à des supports authentiques en anglais, ce qui engendre des difficultés à participer à des conversations réelles. Ce décalage entre les connaissances académiques et leur application concrète conduit généralement à un manque de confiance en soi, de l'hésitation et un faible rendement en communication orale. Cette étude vise à démontrer l’efficacité de l’approche communicative dans l’enseignement (CLT) pour améliorer la compétence orale chez les étudiants EFL. Pour tester l’hypothèse principale selon laquelle l’implémentation de la CLT favorise l’amélioration de l’expression orale, une approche méthodologique mixte combinant méthodes quantitatives et qualitatives a été adoptée. Des observations en classe et des questionnaires ont été réalisés auprès d’un échantillon de 40 étudiants de troisième année (sur un total de 93) ainsi que de 6 enseignants de l’Université de Souk-Ahras. Les observations ont porté sur les modalités d’application de la CLT en contexte de classe et son efficacité dans le développement des compétences orales. En parallèle, le questionnaire a permis de recueillir les attitudes et les besoins des étudiants vis-à-vis du processus d’enseignement-apprentissage, ainsi que les perceptions des enseignants concernant l’approche communicative. Les résultats montrent que l’approche communicative exerce un impact positif sur les compétences orales des apprenants en leur offrant un environnement favorable et rassurant pour l’expression orale.
Keywords: Communicative language teaching; EFL students; oral proficiency; classroom interaction; academic knowledge; teaching-learning process; speaking skill; منهج التدريس التواصلي، طلبة اللغة الإنجليزية كلغة أجنبية، الكفاءة الشفوية، التفاعل الصفي; المعرفة الأكاديمية; عملية التعليم والتعلم; مهارة التحدث; enseignement communicatif; étudiants EFL; compétence orale; interaction en classe; savoir académique; processus d’enseignement-apprentissage; expression orale